Rediscovering the Alcibiades Major - Samuel Oliveira (Outros titulos, 2020)
It is a well-known fact that Kant used the lament of the Trojan queen, Hecuba, from Ovid's Metamorphoses to describe the fate of metaphysics. But these words could equally be used to describe the peculiar fate of the Alcibiades Major. There was a time when this small dialogue was held in high regard and enjoyed much authority.2 The Alcibiades Major was unreservedly attributed to Plato. It was much read, quoted and alluded to. And it is no exaggeration to say that it was one of the key works of the corpus platonicum. The contrast with the present could hardly be more striking.